An Analysis of Income Smoothing Policies’ Effects on The Quality of Accounting Information in Kurdistan Banks - Saifaldeen Khaleel Hamad; Sardar Jalal Braim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The main purpose of the study is to examine income smoothing policies’ effects on the quality of Kurdistan banks’ accounting information. A single regression model was used to analyse income smoothing policies’ effects on the quality of accounting information using 50 financial managers, accounts managers, internal audit managers, administration managers, internal auditors, accountants and general managers’ responses. The findings showed that banks engaging in income smoothing policies stand a huge chance to offer high-quality accounting information. It was further observed that income smoothing policies are a notable determining element of accounting information quality and aid in explaining fluctuations in accounting quality throughout the banking sector. This study also hints that income smoothing policies can positively affect accounting information reliability and credibility, as stakeholders and investors are more likely to trust predictable and stable financial statements. As such, the results have profound theoretical implications for accounting reporting theories, as they indicate that income smoothing policies are a crucial tool for banks to employ to boost the quality and credibility of their financial statements.